Effects of Different Doses of Aspartame on Some Biochemical Parameters of Kidney Rats - Marwa Amer Ali (Journal of Global Pharma Technology, 2018)
This study aims to determine the effect of aspartame on the biochemical parameter, and its influence on the kidney tissues in rats. Thirty adult male rats and 30 adult female rats, with age of 60-65 day are used in this study, almost on an average live weight between (165-200) gm. The experiment concentrates on the daily dose, where the animals are randomly divided into four groups, each group contains 15 animals (five males & ten females), three experiment groups treated and control group. The first group treatment A gavage with concentrated aspartame of (250 mg / kg/ per day), the second group treatment B gavage with concentrated aspartame (500mg/kg/per day) and the third group treatment C dosage of (1000mg/ kg/ per day), while the control group dosed with 1ml physiologic solution daily. All the groups had their daily dosages orally for 90 days, and the study continued from 29 October 2017- 26 January 2018. After the end of experiment , blood sample was collected for estimate this serum of urea ,uric acid and creatinine .The results of this study showed that there is non- significant differences (P> 0.05) in urea concentration between control group and group A,B and C. Also there is non-significant differences (p>0.05) between treatment groups .The result showed there is a significant differences (p<0.01)in creatinine concentration in group A in comparison with control group .But group B showed non- significant differences (p>0.05) in creatinine concentration compared with control group .while group C has a significant increase (p<0.05) in creatinine concentration in compared with control increase (p<0.05) in creatinine concentration in compared with control group. When the treatment groups the results showed that the group A high significant difference (p<0.01) when compared with B group .whereas non -significant differences (p>0.05) between A and C groups. Also there is non- significant differences (p>0.05) between B and C groups. In uric acid showed non- significant differences (p>0.05) compared with group A and control group, Also there is a non-significant decreased (P>0.05) compared with the B group and control group. While showed in the C group has a high significantly differences (p<0.01) compared with the control group .when compared the treatment groups the results showed there is non- significant differences (p>0.05) between group A and B, C groups .Also there is non- significant differences (p>0.05) between B group and C.Keywords: Aspartame and effect on kidney.